2016
DOI: 10.1109/rbme.2016.2555760
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Modulation of Calcium Dynamics Using Ultrasound and Other Energy-Based Techniques

Abstract: Ultrasound, along with other types of energy-based methods, has been widely investigated for use in various therapeutic applications because of its ability to stimulate specific biological processes. Many of these processes are mediated by calcium (Ca2+) signaling, thus making modulation of Ca2+ dynamics an evident therapeutic target for energy-based techniques. Various diseases have been associated with abnormal Ca2+ signaling and could therefore benefit from therapeutic approaches trying to regulate the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 174 publications
0
20
0
Order By: Relevance
“…Further studies are required to determine the exact mechanisms involved in ultrasound-enhanced insulin release from pancreatic beta cells. In addition to cavitation, other mechanisms documented in literature could play an important role in this process (Suarez Castellanos et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to determine the exact mechanisms involved in ultrasound-enhanced insulin release from pancreatic beta cells. In addition to cavitation, other mechanisms documented in literature could play an important role in this process (Suarez Castellanos et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the application of ultrasound to pancreatic beta cells induces up to four fold increases in release of insulin as compared to control, while retaining cell viability [ 24 ]. Further, previous published studies demonstrated that ultrasound application can stimulate calcium transients in cells [ 25 ]. In view of this, we hypothesize that the observed increase in insulin secretion is the result of ultrasound-stimulated calcium influx and the subsequent triggering of insulin vesicle exocytosis [ 26 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that mechanosensory FUS-stimulation generates a robust Ca 2+ signaling response which can be used to distinguish invasive from non-invasive cancer cells (Hwang et al, 2013;Weitz et al, 2017). Others have also demonstrated mechanosensory Ca 2+ signaling responses using non-focused US-stimulation other contexts (Carina et al, 2018;Pan et al, 2018;Wood and Sehgal, 2015) as well as more general studies to clarify the physiological, cell biological and molecular mechanisms underlying mechanosensory dependent Ca 2+ signaling responses (Castellanos et al, 2016;Liu et al, 2017;Maresca et al, 2018;Tyler et al, 2008). Our Removing or lowering external Ca 2+ from culture medium did not eliminate FUS dependent Ca 2+ signaling (see Figure 1D).…”
Section: Discussionmentioning
confidence: 98%